Village Financial Management Strategy in Improving Village Financial Performance in Bogor District: Management Finance Village - Atikah, Raden Muhammad Jiddan Aziz; Yusman Syaukat,; Laily Dwi Arsyianti,; Indupurnahayu,; Renea Shinta Aminda, (Jurnal Manajemen, 2023)
Development changes village for 10 years experience a very rapid increases with the birth of law number 6 of 2014 about village, but Corruption cases in Indonesia are still very high, especially in Bogor Regency there was a case of arrest of the Bogor Regency Regent, 7 reports of misuse of village funds and 1 arrest of the village head who was proven to be a suspect in corruption in village financial management, the existence of this case will affect the village's assessment, especially in its financial performance requires good management in managing finances in order to create good governance, therefore the purpose of this study is the arrangement of village financial management, data processing methods using the Analytical Hierarchy Process (AHP) with a profusive sampling sample including 7 expert judgments to assess strategy, results This research is based on the dominating criterion, namely planning that must be improved, on the sub-criteria, namely village financial independence, and on the alternative strategy chosen, namely strengthening the quality of human resources and regulations, then carrying out managerial implications by strengthening the quadruple helix model approach between the government, academics/experts, business, and society.